Pengetahuan dan Perspektif Masyarakat Lokal Terhadap Schistosomiasis di Indonesia - Ningsi Ningsi; Hayani Anastasia; Made Agus Nurjana; Rina Isnawati; Octaviani Octaviani; Gunawan Gunawan; Ahmad Erlan (Jurnal Vektor Penyakit, 2022)
ABSTRACT Schistosomiasis, also known as snail fever, is caused by a parasitic worm. These parasites emerge from snails (conch) to contaminate fresh water and then infect humans or mammals such as cows, buffalo, and pigs whose skin is in contact with water. Various efforts continue to be encouraged so that cases of schistosomiasis decrease. Methods to prevent disease include increasing access to clean water, reducing snail populations, improving waterways, and the role of local community leaders. This study aimed to explore people's local knowledge and perspectives in endemic schistosomiasis areas. This study uses a cross-sectional design for quantitative and qualitative by collecting data through FGD. With as many FGD participants in each group, as many as ten people. The number of respondents was selected by simple random sampling. The results showed that local people's knowledge was still low, especially about the causes and modes of transmission of schistosomiasis. The community's perspective on controlling schistosomiasis carried out by cross-sectoral and health services and their staff is quite good. Local people expect stockpiling/drying of snail-focused areas, giving PPE boots for free. Local perspectives on the involvement of community leaders are still lacking, especially in community social groups such as PKK and dasawisma. In addition, cross-sectoral collaboration, the health office, and community leaders still need to be improved. The need for strengthening the eradication of schistosomiasis by involving informal, formal leaders in endemic schistosomiasis areas ABSTRAK Schistosomiasis atau disebut juga demam keong, disebabkan oleh parasit cacing. Parasit ini muncul dari siput (keong) untuk mencemari air tawar dan kemudian menginfeksi manusia ataupun hewan mamali. Metode untuk mencegah penyakit ini adalah meningkatkan akses terhadap air bersih, mengurangi populasi keong, perbaikan saluran air, dan peran dari tokoh masyarakat setempat. Tujuan penelitian ini mengeksplorasi pengetahuan dan perspektif lokal masyarakat di daerah endemis schistosomiasis. Peneltian ini menggunakan desain cross-sectional melalui pendekatan kuantitatif dan Kualitatif dengan cara pengumpulan data melalui Focus Group Discussion (FGD). Jumlah peserta FGD masing-masing kelompok sebanyak 10 orang. Jumlah responden 1692 yang dipilih secara simple random sampling. Hasil penelitian menunjukkan, pengetahuan masyarakat lokalmasih rendah khususnya tentang penyebab dan cara penularan schistosomiasis. Persepektif masyarakat tentang pengendalian schistosomiasis yang dilakukan oleh lintas sector dan dinas kesehatan bersama jajarannya sudah cukub baik. Masyarakat lokal mengharapkan penimbunan/ pengeringan areal fokus keong,pemberian Alat Pelindung Diri (APD) sepatu bot secara gratis. Perspektif lokal tentang keterlibatan tokoh-tokoh masyarakat masih kurang terutama kelompok sosial masyarakat seperti Pemberdayaan dan Kesejahteraan Keluarga (PKK) dan dasawisma. Selain itu kerjasama lintas sektor, dinas kesehatan dan tokoh-tokoh masyarakat masih perlu ditingkatkan. Perlunya penguatan dalam pemberantasan schistosomiasis dengan melibatkan tokoh formal nonformal di daerah endemis schistosomiasis.